Efektifitas Pemberian Air Kelapa Muda Dan Slow Deep Breathing Terhadap Kejadian Dismenore Pada Usia Remaja - Nurhayati, Ceria; Ninik Ambar Sari (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
Menstrual pain is a sign of physiological symptoms felt by every woman who is menstruating. Generally, women who are menstruating will experience menstrual pain, but some women feel uncomfortable and even menstrual pain is an obstacle for women in carrying out daily activities. This research aims to determine the effectiveness of young coconut water in treating dysmenorrhea. Research ii is an analytical research which is included in the Quasy Experimental Design. Chi Square because both variables use a nominal data scale. The data collection tool used in this preliminary study is a questionnaire. The results showed that after being given 200 ml of young coconut water every day for 14 days accompanied by Slow Deep Breathing, the incidence of dysmenorrhea in adolescents aged 18-20 years at STIKES Hang Tuah Surabaya decreased to 19 people (32 %) The decrease in the incidence of dysmenorrhea is due to drinking young coconut water given to adolescents aged 18-20 years for 14 consecutive days can provide an alternative to overcome menstrual pain (dysmenorrhea). Suggestions for further research are expected to add to the contribution of knowledge, especially teenagers, about overcoming menstrual pain, one of which is the consumption of young coconut water with a combination of slow deep breathing.